Agricultural development in recent decades and welfare challenges - Niti Mehta (Agricultural Economics Research Review, 2023)
While economic development is dependent on performance of agriculture sector, rural areas have been facing skewed land distribution, falling agricultural investments and rising cost of cultivation. Land fragmentation forces rural households to straddle between employment in agriculture and nonagricultural activities. The paper examines linkages of agricultural growth with overall economy, performance of agricultural sector and declining support to it. Sectoral labour productivity, wage differentials and income are examined to contextualize wellbeing of households across states and size continuum. Policy focus needs to be on measures to aid inclusivity and wellbeing of rural workers.